2011
DOI: 10.1016/j.atmosenv.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rain scavenging on altitudinal distribution of soluble gaseous pollutants in the atmosphere

Abstract: We suggest a model of rain scavenging of soluble gaseous pollutants in the atmosphere. It is shown that below-cloud gas scavenging is determined by non-stationary convective diffusion equation with the effective Peclet number. The obtained equation was analyzed numerically in the case of log-normal droplet size distribution. Calculations of scavenging coefficient and the rates of precipitation scavenging are performed for wet removal of ammonia (NH 3 ) and sulfur dioxide (SO 2 ) from the atmosphere. It is show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…For example, there was moderate rain due to a thunderstorm on 27 August (www.wunderground.com). The wet deposition helps scavenge the aged particles (Nilsson, et al, 2001;Elperin et al, 2011). Fresh emission from vehicles was observed, consistent with the results of Wang et al (2011).…”
Section: Atmossupporting
confidence: 79%
“…For example, there was moderate rain due to a thunderstorm on 27 August (www.wunderground.com). The wet deposition helps scavenge the aged particles (Nilsson, et al, 2001;Elperin et al, 2011). Fresh emission from vehicles was observed, consistent with the results of Wang et al (2011).…”
Section: Atmossupporting
confidence: 79%
“…Rainfall is recognized as one of the main natural processes to improve air quality (Duhanyan and Roustan, 2011;Elperin et al, 2011), and it can greatly enhance the positive reductions achieved by anthropogenic control measures (Leung and Gustafson, 2005). Our previous study assessed the rainfall removal efficiency for total suspended particles (TSP) and found that artificial rain interventions may worsen air quality due to the lower removal of TSP without rainfall (Guo et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…In our previous studies (see, e.g. Elperin et al 2011;Baklanov et al 2013) we showed that accounting for the droplet size distribution does not lead to significant changes in the rate of gas scavenging in comparison with that calculated using the average radius approximation. Therefore, in the present study we performed calculations for the monosize droplets having the average rain droplet radius.…”
Section: Introductionmentioning
confidence: 92%
“…Equation of mass balance for soluble trace gas in the gaseous and liquid phases reads (Elperin et al 2011):…”
Section: Absorption Scavenging Of Soluble Gases Accompanied By Aqueoumentioning
confidence: 99%